Critical causes factor of fall accident in construction site - Norasima, Jamaludin (2010)
The construction industries are a very dangerous environment which had a history of a relatively high number of injuries in comparison of other industries.Work at the high level has a tendency to involve in fall accident.Falls accident is one of the major leading causes of work facilities that occur to labor in the construction site.The aim of this study to investigate the safety problem in construction site,then identify the critical cause factor of fall accident in construction site,the solution and analysis the factors.The data was collected through interview,industrial visit,constructed and distiburted questionnaire in order to indentify the safety requirements in construction site.All of the interview and research questionnaire survey are conducted among contractor in company area Kuala Lumpur and Kuantan,Pahang.Returned questionnaire were analyses with average index to rank the factor of causes fall accident and frequency analysis method to identify the safety aspect in construction site.From the analysis find that unsafe behavior is the critical causes of fall accident in costruction site.In conclusion with existance of this study, it can boost up knowledge about safety and the company can be aware to prevent the fall accident from happen in the construction site.